2-7x-8=-13

Simple and best practice solution for 2-7x-8=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-7x-8=-13 equation:


Simplifying
2 + -7x + -8 = -13

Reorder the terms:
2 + -8 + -7x = -13

Combine like terms: 2 + -8 = -6
-6 + -7x = -13

Solving
-6 + -7x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -7x = -13 + 6

Combine like terms: -6 + 6 = 0
0 + -7x = -13 + 6
-7x = -13 + 6

Combine like terms: -13 + 6 = -7
-7x = -7

Divide each side by '-7'.
x = 1

Simplifying
x = 1

See similar equations:

| 20x^4-5x^2=0 | | -sin(16x)=0 | | 828b*-22=18 | | 3x-5(x-2)=-6+5x-26 | | -2(5h-9)=17+3h | | 9p-7+6p-5= | | 2((r)(r)+1)=5r | | -27+8a=6(2a-3) | | .20(50)= | | 0.2(1.53+5x)=1.6x | | 2((r)+1)=5r | | 11x-26-5x=58 | | -7+2i= | | 5x^2-7x=12 | | 3(2x-14)=-40 | | -6v-3v=-18 | | 0.2(1.53+5x)=16x | | 9h-8+2+6s= | | -3(9s+6)=-35 | | 7(2x-1)+5(2-3x)=2x | | -4x-38+7x=19 | | 0.2(1.53+5x)=16 | | 3x-6+7=25 | | 2x=6x+16 | | 9+2f+7-3r= | | 2x^2-8x=8 | | 1+x-1=-6 | | (s)(s)(s)-(s)(s)= | | 50-17=15 | | 2.8=18x | | [5u-15]=10 | | 24=-(18-7x) |

Equations solver categories